Duration of labor, delivery mode and maternal and neonatal morbidity after remifentanil patient-controlled analgesia compared with epidural analgesia. (April 2020) - Thorbiörnson, Anna; da Silva Charvalho, Paula; Gupta, Anil; Stjernholm, Ylva Vladic
Abstract: Objective: The objective of this study was to compare duration of active labor, delivery mode, maternal and neonatal morbidity and women's satisfaction with delivery after intravenous remifentanil patient-controlled analgesia (PCA) or standard epidural analgesia (EDA). Based on clinical observations, we hypothesized that women with PCA would have shorter labor. Study design: An observational study at a university hospital in Sweden 2009–16. Maternal and neonatal outcomes with PCA (n = 69) and EDA (n = 138) were compared. Results: Women with PCA had shorter active labor 5.6 ± 3.3 compared to 8.5 ± 4.4 h (p < 0.001) with EDA, and a higher rate of spontaneous delivery 94% (65/69) compared to 65% (n = 90/138) with EDA (p < 0.001). Intrapartum temperature >38 °C (p = 0.001) and signs of fetal asphyxia (p < 0.001) were less common with PCA. No maternal or neonatal sedation was observed. The rates of transient oxygen desaturation <95%, bleeding > 1000 mL and women's satisfaction with delivery did not differ between the groups. Conclusion: PCA had several advantages over EDA, as it was associated with shorter active labor and a higher rate of spontaneous delivery without worsening maternal or neonatal morbidity or women's satisfaction with delivery. Therefore, we suggest an increased availability of PCA for labor analgesia. We recommend continuous one-to-one care and oxygen saturation monitoring for all women during active labor.